IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESRIPTIVE PARAGRAPH BY USING MOVIE POSTERS - Tengku Nova Mulyana; Masitowarni Siregar (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
ABSTRACTThis study aims at improving students’ achievement in writing descriptive paragraph by using Movie Posters. This study was conducted by using classroom action research. The subject of the research was class X SMA Negeri I Galang, which consist of 36 students. The research was conducted in two cycles which cycle I and cycle II consist of 3 meetings. The instruments for collecting data were qualitative (interview, diary notes, and observation sheet) and quantitative data(writing test). Based on the data analysis, the mean of students’ score in Test I was 56,38 ; for the Test II was 68,05 , and for the Test III was 85. The qualitative data showed that the students were interested by using Movie Posters. The conclusion is that by using Movie Posters improves the students’ achievement in writing descriptive. Keywords: Movie Posters, Classroom Action Research, Writing Descriptive Paragraph